The Power of Collegiality A Qualitative Analysis of University Presidents' Leadership in Germany - Bieletzki, Nadja (Organization & Public Management, 2018)
Nadja Bieletzki explores how university presidents lead universities. She provides insights into the upper echelons of higher education management and focuses especially on university presidents in Germany. Special attention is given to the career background of university presidents and the way they conduct reform projects. Based on the results from semi-structured expert interviews and their qualitative analysis, the author shows that university presidents do not use all their formal power although their position has been strengthened by law. This can be explained by the collegial characteristics of universities, which drive and restrict presidential actions. Contents Analyzing Higher Education Management Career Paths of University Presidents Understanding Reforms in Universities with Micro/Organizational Politics Target Groups Researchers and students in the fields of sociology and political sciences with a focus on higher education research and science studies Science managers at higher education and research institutions as well as ministries with an interest in scientific results of higher education research The Author Dr. Nadja Bieletzki is coordinator of the Leibniz Center for Science and Society (LCSS) at the Leibniz University of Hannover. .